Velhice e alteridade: a relação entre os asilados e as "senhoras da caridade" - Silva, Kátia Ramos (2012)
This paper has like main reason to analyse the oldness through the perspective of alterity. Looking for knowing the differences that mark the experiences of getting old in the modern society through practices which were developped by old voluntary women of a charity association, close to old people who live in an asylum in the city of Campina Grande - PB. The Associação Internacional de Caridades (AIC - Charity International Association), core of Campina Grande - PB,it corresponds to a feminine, lay organization composed mostly by old women of middle class in which attends to socialy excluded segments, between them, old people in asylums. The meeting between oldness make possible that old people inserted in these groups and contexts prepare a self-image, stablish relations of gerational sociability and exercise the principle of alterity constructed in the interpersonal relation between myself and the other in oldness. The heterogeneus character that distinguish the old person in the present time, discussed by scholars, is spotlightened in the research that was realized. The stablished relationship between the cheritable and the refugee reveals multiple meanings that involve the oldness and enlighten the aspects of subjectivity and identity of the old people who integrate the reported groups.